IMAGING OF VASCULAR ANOMALIES OF THE AORTA AND VESSELS OF THE HEAD AND NECK- REVIEW ARTICLE - Kostic, Jelena; Cvetic, Vladimir; Mladenovic- Markovic, Ana; Vukasinovic, Ivan (Medical Research, 2026)
This review article aims to present the most common vascular anomalies of the head and neck arteries, detailing their clinical presentations, the diagnostic advantages of current imaging modalities, and the selection of appropriate therapeutic interventions. Vascular malformations result from localized errors in the development of blood and lymphatic vessels, leading to the formation of abnormal structures prior to birth. They typically grow proportionally with the child, though they may occasionally undergo rapid expansion. Vascular malformations are classified based on their hemodynamic characteristics into two major categories: slow-flow anomalies (comprising capillary, lymphatic, and venous malformations) and fast-flow anomalies (arteriovenous and arterial malformations). The incidence of arteriovenous malformations (AVMs) is increasing; many remain clinically asymptomatic, though approximately 12% are symptomatic. In cases involving hemorrhage, the mortality rate is 10–15%, with morbidity ranging from 30% to 50%. There is no gender predilection. Computed Tomographic Angiography (CTA) and Magnetic Resonance Imiging (MRI) are essential for therapeutic planning and risk assessment across surgical, endovascular, and radiological interventions. These modalities allow for the visualization of complications such as hemorrhage, stroke, and cerebral atrophy. Furthermore, magnetic resonance imaging is critical for assessing the reduction of the nidus size, the extent of post-therapeutic edema, and the presence of radiation necrosis within the treatment field. While surgery remains the primary definitive treatment, embolization has become a significant therapeutic component in recent years.
Keywords: Key words: arterial-venous malformations, computerised tomography, magnetic resonance imaging, aneurysm and venous dysplasia.